Answer:
x = -3±sqrt( 5)
Step-by-step explanation:
(x + 3)^2-5=0
Add 5 to each side
(x + 3)^2-5+5=0+5
(x + 3)^2 = 5
Take the square root of each side
sqrt((x + 3)^2 )=±sqrt( 5)
x+3 = ±sqrt( 5)
Subtract 3 from each side
x+3-3 = -3±sqrt( 5)
x = -3±sqrt( 5)
F(f-1x) will be equal to x
take a simple example
f(x) = 2x
so x = f(x) / 2
f-1(x) = x/2
f(f-1x) = 2 ( x/2) = 2 * x/2 = x
Answer:
7
Step-by-step explanation:
Answer:
D. 564.44 cm^3
Step-by-step explanation:
V = (1/3)(pi)r^2h
V = (1/3)(3.14159)(7 cm)^2(11 cm)
V = 564.44 cm^3
Answer:
23 feet
Step-by-step explanation:
The absolute value of -14 is fourteen.
The absolute value of 23 is twenty-three
23>14